Higher Education and Student Employment Needs - Beach, Horace D. (Canadian Journal of Higher Education, 1977)
Harold Macmillan, former Prime Minister of the United Kingdom, recounted what an Oxford professor said back in the thirties about higher education. The professor introduced his course with these words: (14) Gentlemen — you are now about to embark upon a course of studies which will occupy you for two years. Together they form a noble adventure. But I would like to remind you of an important point. Some of you, when you go down from the University will go into the Church, or to the Bar, or to the House of Commons, to the Home Civil Service, to the Indian or Colonial Services, or into various professions. Some may go into the Army, some into industry and commerce; some may become country gentlemen. A few - I hope very few — will become teachers or dons. Let me make this clear to you. Except for the last category, nothing that you will learn in the course of your studies will be of the slightest possible use to you in after life save only this - that if you work hard and intelligently, you should be able to detect when a man is talking rot, and that, in my view, is the main, if not the sole purpose, of education. This is one view of higher education, and an important view. However, there is a here- after for college and university students, in which they must survive and carry on. In this paper I shall focus on the employment aspect of the hereafter. What is the impact of a college or university education on students' future employment?